Pelatihan Bahasa Inggris, English For Direction, Bagi Pemuda Karang Taruna Di Desa Mekarbuana - Vidya Arisandi; Ajat Sudrajat; Daffa Adam Yudistira; Mohammad Bagas Prakoso; Siti Julaeha H.S (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
A community service project aims to improve the English skills of Karang Taruna members in Mekar Buana, Tegal Waru, and Karawang as part of this community service project. A skill improvement program focuses on improving the ability to speak English with a strong emphasis on the concept of direction in the context of spoken English. The training is based on discussion and practice in which the methods used are discussion and practice. So that in the end, this service can be seen as having a goal, that is, when the skills of cadet reef members, which tend to be dominated by these young people, can be enhanced with time, they can become a liaison between Mekarbuana villagers and foreign tourists who come to the village in the future.